Determination of fear of covid-19 and distress levels of pregnant women admitted to obstetrics emergency departments - POTUR, DİLEK (My University, 2023)
Background. The aim of this study was to determine the fear of Covid-19 and pregnancy distress levels experienced by pregnant women who were admitted to the obstetrics emergency service during the pandemic. Material and methods. This descriptive study was conducted using the face-to-face interview technique with 194 pregnant women who met the inclusion criteria of the study and were admitted to the Obstetrics Emergency Service of the University of Health Sciences Zeynep Kamil Gynecology and Pediatrics Training and Research Hospital in Türkiye between December 2020 and February 2021. Results. The mean age of the pregnant women included in the study was 28.37, and 51.1% of them were found to be multiparous. The mean Fear of Covid-19 Scale (FCV-19S) of the pregnant women was 19.50±6.64 and the mean Tilburg Pregnancy Distress Scale (TPDS) was 34.79±6.82. It was determined that the educational status of the pregnant women differed statistically significantly (p<0.05) according to the FCV-19S. It was found that there is a positive and strong relationship between the FCV-19S and the TPDS (r=0.216; p=0.002) and “Negative Affect” (r=0.211; p=0.003). Conclusions. During the Covid-19 pandemic period, the Covid-19 fear and distress levels of the pregnant women who were admitted to the Obstetrics Emergency Service were determined as moderate. Since the fear of Covid-19 has an effect on pregnancy distress levels, it is recommended that nurses should be aware of the distress experienced by pregnant women and be their pregnancy support

Wprowadzenie. Celem niniejszego badania było określenie lęku przed Covid-19 oraz poziomu stresu ciążowego u ciężarnych kobiet, które zostały przyjęte na położnicze oddziały ratunkowe w trakcie pandemii. Materiał i metody. Niniejsze opisowe badanie zostało przeprowadzone techniką wywiadu bezpośredniego z 194 kobietami ciężarnymi, które spełniły kryteria włączenia do badania i zostały przyjęte na położniczy oddział ratunkowy szpitala Zeynep Kamil Gynecology and Pediatrics Training and Research Hospital Uniwersytetu Nauk o Zdrowiu w Turcji w okresie od grudnia 2020 do lutego 2021 r. Wyniki. Średni wiek kobiet ciężarnych objętych badaniem wynosił 28,37 lat, z czego 51,1% okazało się być wieloródkami. Średni wynik w skali lęku przed Covid-19 (SLCV-19) u kobiet w ciąży wyniósł 19,50±6,64, a średni wynik w skali poziomu stresu u kobiet ciężarnych Tilburga (SPSKCT) wyniósł 34,79±6,82. Stwierdzono, że status edukacyjny ciężarnych różnił się w sposób istotny statystycznie (p<0,05) według SLCV-19. Zaobserwowano, że istnieje pozytywny i silny związek między wynikiem w SLCV-19 oraz w SPSKCT (r=0,216; p=0,002) a „Afektem Negatywnym” (r=0,211; p=0,003). Wnioski. W okresie pandemii Covid-19, poziom lęku przed Covid-19 i stresu u kobiet ciężarnych przyjętych na położniczy oddział ratunkowy określono jako umiarkowany. Ponieważ lęk przed Covid-19 ma wpływ na poziom stresu związanego z ciążą, zaleca się, aby pielęgniarki były świadome stresu doświadczanego przez kobiety w ciąży i stanowiły dla nich wsparcie
Określenie poziomu lęku przed covid-19 I stresu u kobiet ciężarnych przyjmowanych na położnicze oddziały ratunkowe
Keywords: Hemşirelik; Kadın Hastalıkları ve Doğum Hemşireliği; Sağlık Bilimleri; Nursing; Gynecology and Obstetrics Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Covid-19; stres; położnictwo; pogotowie; ciąża; pielęgniarstwo; distress; obstetrics; emergency; pregnancy; nursing